Manejo adaptativo e apropriação de sistemas agroflorestais por agricultores através do monitoramento participativo - Rosa, Samuel Carvalho Ferreira da [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The present essay has conducted a process of participatory action research with a few farmers from Raposa community and Rio Preto community, both located in the town of Sete Barras, which is inserted in the complex social and environmental reality of the Vale do Ribeira. The studied Agroforestry Systems (SAF) were implemented by the project SAF Juçara, which has been promoting the cultivation of Juçara palm tree within SAF for the extraction and commercialization of the pulp, as a conservation strategy of this species. This process was dedicate to describe the agroecosystems of the essay, built with the farmers an agroforestry monitoring system using participatory methodologies, apply the system that was built and then evaluate this for the necessary improvements. It was noted that throughout the participatory monitoring process, the farmers have come to a better understanding of the development dynamics of their productive systems, and then they started the process of appropriation as manegment of these systems, being capable to apply the adaptive management of their SAF. As a product of this essay, a monitoring booklet for Agroforestry Systems has been developed to allow the maintenance of the monitoring as well as the replication of this process with other farmers

O presente trabalho conduziu um processo de pesquisa-ação participativa com alguns agricultores da comunidade do Raposa e do Rio Preto localizadas no município de Sete Barras, o qual está inserido na complexa realidade socioambiental do Vale do Ribeira. Os Sistemas Agroflorestais estudados foram implementados pelo projeto SAF Juçara, que busca promover o cultivo da palmeira Juçara em SAF, para obtenção e comercialização da polpa, como estratégia de conservação desta espécie. Este processo dedicou-se a descrever os agroecossistemas em estudo, construir com os agricultores um sistema de monitoramento agroflorestal através de metodologias participativas, aplicar o sistema elaborado e depois avaliá-lo para os devidos aperfeiçoamentos. Notou-se que ao longo do monitoramento participativo, os agricultores puderam entender melhor a dinâmica de desenvolvimento de seus sistemas produtivos, e assim iniciaram o processo de apropriação e gestão dos mesmos, sendo capazes de realizar o manejo adaptativo de seus SAF. Como produto desta pesquisa, confeccionou-se uma cartilha de monitoramento participativo de SAF que permite a continuidade do monitoramento e a possibilidade de replicação deste processo com outros agricultores
Keywords: Ecologia vegetal; Ecologia agrícola; Ecologia florestal; Sustentabilidade; Trabalhadores rurais; Palmeira